Microwave-assisted biosynthesis of silver nanoparticles using two marine microalgal extracts and their antimycobacteriosis activity against bacteria isolated from Betta splendens - Piyapan Manklinniam; Saranya Phunpruch; Aparporn Sakulkalavek; Rachsak Sakdanuphab; Worakrit Worananthakij (Scientific Reports)
Abstract This study explores the synthesis and antibacterial properties of silver nanoparticles (AgNPs) as a safer, eco-friendly alternative to traditional chemical treatments for bacterial infections. AgNPs were synthesized using aqueous extracts of marine microalgae, Isochrysis galbana and Chaetoceros calcitrans, via conventional and microwave-assisted methods, with the latter accelerating nanoparticle production. Extracts in ethanol, hexane, and acetone were tested, with the ethanolic extract of I. galbana showing the strongest antibacterial effects. The AgNPs exhibited broad-spectrum antibacterial activity against pathogens such as Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, and fish pathogens like Aeromonas veronii. Microwave-assisted synthesis with ethanolic extracts resulted in the highest inhibition, particularly against fish and tuberculosis-related pathogens, including Mycobacterium marinum. Nanoparticle formation was confirmed using various characterization methods, including ultraviolet-visible (UV-Vis) spectroscopy, X-ray diffraction (XRD), fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), which revealed crystalline structures. Transmission electron microscopy (TEM) analysis revealed that AgNPs varied in size, with an average diameter of less than 50 nm and all particles being smaller than 100 nm. This research demonstrates the potential of AgNPs as an effective alternative to antibiotics, offering targeted bacterial inhibition while reducing the risk of antibiotic resistance. This makes it a promising approach for treating bacterial infections in ornamental fish.